India: A Framework for Design of Energy Critical Infrastructure to Inform Disaster Policy Making - Hancock, Linda; Cherian, Mathew (Journal of Environmental Accounting and Management, 2026)
This research aimed to construct a framework to guide policy decisionmaking for climate compatible resilient energy systems, appropriate for countries prone to disasters. It followed a method based on a literature review and the applied example of India. Part I of the framework comprised a snap-shot of a country or regional energy source mix, an overview of energy policies/politics and an outline of the challenges of RE and policy design for more resilient energy systems in disaster-prone regions. Using secondary analysis of official Indian energy system data, the research demonstrated the challenges of energy transitions for a developing country highly dependent on fossil fuels. Part II further developed key elements of the framework, structured around key concepts of climate compatible critical infrastructure, technology based on ethical materials choices used in energy generation devices and energy systems, development of disaster risk resilience (DRR), governance and public policy analytical lenses for design of climate compatible resilient disaster energy systems, and finally, identification of criteria for assessing the ongoing sustainability of energy systems. The framework was designed to assist policy makers by laying out steps to address the proactive design of disaster and climate change compatible energy systems and critical infrastructure.